Using image analysis to assess the contributions of plankton and particles to tropical coastal ecosystems. (5th April 2019) - Lins Silva, Nathália; Marcolin, Catarina R.; Schwamborn, Ralf
Abstract: Suspended particulate matter (seston) in aquatic ecosystems contains two compartments: organisms (plankton) and particles. To know the contribution of particles to the pelagic realm is essential to understand the structure and dynamics of aquatic ecosystems. This study aims to determine the relative contribution of particles to the meso-sized seston biomass in plankton samples obtained with common plankton nets (meshes: 200 and 300 μm) comparing wet weight measurements and image analysis using a ZooScan equipment. Samples were obtained in Tamandaré Bay and in the Rio Formoso estuary (Pernambuco, Brazil) during two years (June/2013 to May/2015) at bi-monthly intervals during dry and rainy seasons, totalizing 155 samples. The estuarine environment had the highest values of wet meso-seston biomass, abundance, and volume. In the estuary, the relative contribution of particles in volume units (>55%) was higher than zooplankton. In the bay surrounded by coral reefs, relative particle volume was lower than in the estuary, but still very important (36.86% and 52.15% in the 200 and 300 μm nets, respectively). Zooplankton and particles were more abundant during the dry season. We found significant and positive linear relationships (r 2  = 0.68; p < 0.0001), indicating that ZooScan-derived volume data can be confidently used to estimate wet biomass. This study provides a novel approach for the analysis of non-fragile mesoparticles and mesozooplankton in estuarine and marine ecosystems, based on sampling with plankton nets and subsequent analysis with imaging systems. This approach allows new interpretations on the composition of large-sized, robust seston in tropical areas.